(untitled) (Journal of Namibian Studies : History Politics Culture, 2021)
Review of: Christopher Hope, Developmentalism, Dependency, and the State. Industrial Development and Economic Change in Namibia since 1900, Basel, Basler Afrika Bibliographien, 2020.